A guided and unguided internet- and mobile-based intervention for chronic pain: Health economic evaluation alongside a randomised controlled trial - Paganini, Sarah; Lin, Jiaxi; Kählke, Fanny; Buntrock, Claudia; Leiding, Delia; Ebert, David; Baumeister, Harald (BMJ Open, 2019)
Objective This study aims at evaluating the cost-effectiveness and cost-utility of a guided and unguided internet-based intervention for chronic pain patients (ACTonPain guided and ACTonPain unguided) compared with a waitlist control group (CG) as well as the comparative cost-effectiveness of the guided and the unguided version. Design This is a health economic evaluation alongside a three-arm randomised controlled trial from a societal perspective. Assessments were conducted at baseline, 9 weeks and 6 months after randomisation. Setting Participants were recruited through online and offline strategies and in collaboration with a health insurance company. Participants 302 adults (≥18 years, pain for at least 6 months) were randomly allocated to one of the three groups (ACTonPain guided, ACTonPain unguided, CG). Interventions ACTonPain consists of seven modules and is based on Acceptance and Commitment Therapy. ACTonPain guided and ACTonPain unguided only differ in provision of human support. Primary and secondary outcome measures Main outcomes of the cost-effectiveness and the cost-utility analyses were meaningful change in pain interference (treatment response) and quality-adjusted life years (QALYs), respectively. Economic evaluation estimates were the incremental cost-effectiveness and cost-utility ratio (ICER/ICUR). Results At 6-month follow-up, treatment response and QALYs were highest in ACTonPain guided (44% and 0.280; mean costs = €6,945), followed by ACTonPain unguided (28% and 0.266; mean costs = €6,560) and the CG (16% and 0.244; mean costs = €6,908). ACTonPain guided vs CG revealed an ICER of €45 and an ICUR of €604.ACTonPain unguided dominated CG. At a willingness-to-pay of €0 the probability of being cost-effective was 50% for ACTonPain guided (vs CG, for both treatment response and QALY gained) and 67% for ACTonPain unguided (vs CG, for both treatment response and QALY gained). These probabilities rose to 95% when society's willingness-to-pay is €91,000 (ACTonPain guided) and €127,000 (ACTonPain unguided) per QALY gained. ACTonPain guided vs ACTonPain unguided revealed an ICER of €2,374 and an ICUR of €45,993. Conclusions Depending on society's willingness-to-pay, ACTonPain is a potentially cost-effective adjunct to established pain treatment. ACTonPain unguided (vs CG) revealed lower costs at better health outcomes. However, uncertainty has to be considered. Direct comparison of the two interventions does not indicate a preference for ACTonPain guided. Trial registration number DRKS00006183.
CRIS-Team Scopus Importer:2019-05-02

A health economic outcome evaluation of an internet-based mobile-supported stress management intervention for employees. - Ebert, David; Kählke, Fanny; Buntrock, Claudia; Berking, Matthias; Smit, Filip; Heber, Elena; Baumeister, Harald; Funk, Burkhardt; Riper, Heleen; Lehr, Dirk (Scandinavian Journal of Work Environment & Health, 2018)
Objective This study aimed to estimate and evaluate the cost-effectiveness and cost-benefit of a guided internet- and mobile-supported occupational stress-management intervention (iSMI) for employees from the employer's perspective alongside a randomized controlled trial. Methods A sample of 264 employees with elevated symptoms of perceived stress (Perceived Stress Scale, PSS-10 ≥22) was randomly assigned either to the iSMI or a waitlist control (WLC) group with unrestricted access to treatment as usual. The iSMI consisted of seven sessions of problem-solving and emotion-regulation techniques and one booster session. Self-report data on symptoms of perceived stress and economic data were assessed at baseline, and at six months following randomization. A cost-benefit analysis (CBA) and a cost-effectiveness analysis (CEA) with symptom-free status as the main outcome from the employer's perspective was carried out. Statistical uncertainty was estimated using bootstrapping (N=5000). Results The CBA yielded a net-benefit of EUR181 [95% confidence interval (CI) -6043-1042] per participant within the first six months following randomization. CEA showed that at a willingness-to-pay ceiling of EUR0, EUR1000, EUR2000 for one additional symptom free employee yielded a 67%, 90%, and 98% probability, respectively, of the intervention being cost-effective compared to the WLC. Conclusion The iSMI was cost-effective when compared to WLC and even lead to cost savings within the first six months after randomization. Offering stress-management interventions can present good value for money in occupational healthcare.

Assessing the costs and cost-effectiveness of ICare internet-based interventions (protocol) - Beecham, Jennifer; Bonin, Eva-Maria; Goerlich, Dennis; Banos, Rosa; Beintner, Ina; Buntrock, Claudia; Bolinski, Felix; Botella, Cristina; Ebert, David; Herrero, Rocio; Potterton, Rachel; Riper, Heleen; et al. (Internet Interventions, 2019)
Background: Mental health problems are common and place a burden on the individual as well as on societal resources. Despite the existence of evidence-based treatments, access to treatment is often prevented or delayed due to insufficient health care resources. Effective internet-based self-help interventions have the potential to reduce the risk for mental health problems, to successfully bridge waiting time for face-to-face treatment and to address inequities in access. However, little is known about the cost-effectiveness of such interventions. This paper describes the study protocol for the economic evaluation of the studies that form the ICare programme of internet-based interventions for the prevention and treatment of a range of mental health problems.
CRIS-Team WoS Importer:2019-03-15

A systematic review of trial-based economic evaluations of internet- and mobile-based interventions for substance use disorders - Buntrock, Claudia; Kählke, Fanny; Smit, Filip; Ebert, David (European Journal of Public Health, 2021)
BACKGROUND: Substance use disorders (SUDs) contribute significantly to global rates of morbidity and mortality. Internet- and mobile-based interventions (IMIs) have been suggested as an adjunct to face-to-face health services. However, the evidence for the cost-effectiveness of IMIs for SUDs is scant. METHODS: A comprehensive literature search in PubMed, PsycINFO, the Cochrane Central Register of Controlled Trials, NHS Economic Evaluations Database, NHS Health Technology Assessment Database, Office of Health Economics Evaluations Database and EconLit was conducted. We included economic evaluations alongside randomized controlled trials of IMIs for SUDs compared with a control group. RESULTS: Of 1687 abstracts identified, 11 studies met the inclusion criteria. Targeted conditions were alcohol use disorder (four studies) and tobacco smoking (five studies) whereas two studies included any SUD. Cost-effectiveness results demonstrated that IMIs had a firm probability of being more cost-effective than TAU (e.g. less costs per additional abstinent person). Compared with (online) psycho-education, evidence towards an additional benefit of IMIs was less clear. Regarding cost-utility (e.g. costs per quality-adjusted life year gained), except for one study, results suggested that TAU and online psycho-education would probably be more preferable than IMIs. Quality of study reporting was at least adequate. CONCLUSIONS: The likelihood of IMIs being more cost-effective than TAU looks promising but more economic evaluations are needed in order to determine the economic merit of IMIs. With an increasing pressure on health care budgets, strategies to disseminate effective interventions at affordable costs are required. This review suggests that IMIs might carry that promise and have potential as a cost-effective strategy to scale-up existing evidence-based treatments for SUDs. SYSTEMATIC REVIEW REGISTRATION: The systematic review has been registered in the PROSPERO database (no. CRD42018099486).
CRIS-Team Scopus Importer:2021-08-20

A Universal Digital Stress Management Intervention for Employees: Randomized Controlled Trial with Health-Economic Evaluation - Freund, Johanna; Smit, Filip; Lehr, Dirk; Zarski, Anna-Carlotta; Berking, Matthias; Riper, Heleen; Funk, Burkhardt; Ebert, David Daniel; Buntrock, Claudia (Journal of Medical Internet Research, 2024)
BACKGROUND: Stress is highly prevalent and known to be a risk factor for a wide range of physical and mental disorders. The effectiveness of digital stress management interventions has been confirmed; however, research on its economic merits is still limited. OBJECTIVE: This study aims to assess the cost-effectiveness, cost-utility, and cost-benefit of a universal digital stress management intervention for employees compared with a waitlist control condition within a time horizon of 6 months. METHODS: Recruitment was directed at the German working population. A sample of 396 employees was randomly assigned to the intervention group (n=198) or the waitlist control condition (WLC) group (n=198). The digital stress management intervention included 7 sessions plus 1 booster session, which was offered without therapeutic guidance. Health service use, patient and family expenditures, and productivity losses were self-assessed and used for costing from a societal and an employer's perspective. Costs were related to symptom-free status (PSS-10 [Perceived Stress Scale] score 2 SDs below the study population baseline mean) and quality-adjusted life years (QALYs) gained. The sampling error was handled using nonparametric bootstrapping. RESULTS: From a societal perspective, the digital intervention was likely to be dominant compared with WLC, with a 56% probability of being cost-effective at a willingness-to-pay (WTP) of €0 per symptom-free person gained. At the same WTP threshold, the digital intervention had a probability of 55% being cost-effective per QALY gained relative to the WLC. This probability increased to 80% at a societal WTP of €20,000 per QALY gained. Taking the employer's perspective, the digital intervention showed a probability of a positive return on investment of 78%. CONCLUSIONS: Digital preventive stress management for employees appears to be cost-effective societally and provides a favorable return on investment for employers. TRIAL REGISTRATION: German Clinical Trials Register DRKS00005699; https://drks.de/search/en/trial/DRKS00005699.
CRIS-Team Scopus Importer:2024-11-01
Keywords: cost-benefit; cost-effectiveness; cost-utility; economic evaluation; employees; internet-based; return-on-investment; stress management; universal prevention

A Web- and Mobile-Based Intervention for Comorbid, Recurrent Depression in Patients With Chronic Back Pain on Sick Leave (Get.Back): Pilot Randomized Controlled Trial on Feasibility, User Satisfaction, and Effectiveness - Schlicker, Sandra; Baumeister, Harald; Buntrock, Claudia; Sander, Lasse; Paganini, Sarah; Lin, Jiaxi; Berking, Matthias; Lehr, Dirk; Ebert, David (JMIR Mental Health, 2020)
Background: Chronic back pain (CBP) is linked to a higher prevalence and higher occurrence of major depressive disorder (MDD) and can lead to reduced quality of life. Unfortunately, individuals with both CBP and recurrent MDD are underidentified. Utilizing health care insurance data may provide a possibility to better identify this complex population. In addition, internet-and mobile-based interventions might enhance the availability of existing treatments and provide help to those highly burdened individuals.
CRIS-Team WoS Importer:2020-05-12

Children of Mentally III Parents at Risk Evaluation (COMPARE): Design and Methods of a Randomized Controlled Multicenter Study-Part I - Christiansen, Hanna; Reck, Corinna; Zietlow, Anna-Lena; Otto, Kathleen; Steinmayr, Ricarda; Wirthwein, Linda; Weigelt, Sarah; Stark, Rudolf; Ebert, David; Buntrock, Claudia; Krisam, Johannes; Klose, Christina; et al. (Frontiers in Psychiatry, 2019)
Objectives: Mental disorders are frequent, associated with disability-adjusted life years, societal, and economic costs. Children of parents with a mental illness (COPMI) are at an increased risk to develop disorders themselves. The transgenerational transmission of mental disorders has been conceptualized in a model that takes parental and family factors, the social environment (i.e., school, work, and social support), parent-child-interaction and possible child outcomes into account. The goal of the "Children of Mentally Ill Parents At Risk Evaluation" (COMPARE) study will thus be twofold: (1) to establish the efficacy and cost-effectiveness of a high-quality randomized controlled trial (RCT) with the aim of interrupting the intergenerational transmission of mental disorders in COPMI, (2) to test the components of the trans-generational transmission model of mental disorders.
CRIS-Team WoS Importer:2019-04-09

Clinical and cost-effectiveness of a guided internet-based Acceptance and Commitment Therapy to improve chronic pain-related disability in green professions (PACT-A): study protocol of a pragmatic randomised controlled trial - Terhorst, Yannik; Braun, Lina; Titzler, Ingrid; Buntrock, Claudia; Freund, Johanna; Thielecke, Janika; Ebert, David; Baumeister, Harald (BMJ Open, 2020)
INTRODUCTION: Chronic pain is highly prevalent, associated with substantial personal and economic burdens, and increased risk for mental disorders. Individuals in green professions (agriculturists, horticulturists, foresters) show increased prevalence of chronic pain and other risk factors for mental disorders. Available healthcare services in rural areas are limited. Acceptance towards face-to-face therapy is low. Internet and mobile-based interventions (IMIs) based on Acceptance and Commitment Therapy (ACT) might be a promising alternative for this population and may enable effective treatment of chronic pain. The present study aims to evaluate the clinical and cost-effectiveness of an ACT-based IMI for chronic pain in green professions in comparison with enhanced treatment as usual (TAU+). METHODS AND ANALYSIS: A two-armed pragmatic randomised controlled trial will be conducted. Two hundred eighty-six participants will be randomised and allocated to either an intervention or TAU+ group. Entrepreneurs in green professions, collaborating spouses, family members and pensioners with chronic pain are eligible for inclusion. The intervention group receives an internet-based intervention based on ACT (7 modules, over 7 weeks) guided by a trained e-coach to support adherence (eg, by positive reinforcement). Primary outcome is pain interference (Multidimensional Pain Interference scale; MPI) at 9 weeks post-randomisation. Secondary outcomes are depression severity (Quick Inventory Depressive Symptomology; QIDS-SR16), incidence of major depressive disorder, quality of life (Assessment of Quality of Life; AQoL-8D) and possible side effects associated with the treatment (Inventory for the Assessment of Negative Effects of Psychotherapy; INEP). Psychological flexibility (Chronic Pain Acceptance Questionnaire, Committed Action Questionnaire, Cognitive Fusion Questionnaire) will be evaluated as a potential mediator of the treatment effect. Furthermore, mediation, moderation and health-economic analyses from a societal perspective will be performed. Outcomes will be measured using online self-report questionnaires at baseline, 9-week, 6-month, 12-month, 24-month and 36-month follow-ups. ETHICS AND DISSEMINATION: This study was approved by the Ethics Committee of the University of Ulm, Germany (file no. 453/17-FSt/Sta; 22 February 2018). Results will be submitted for publication in peer-reviewed journals and presented at conferences. TRIAL REGISTRATION NUMBER: German Clinical Trial Registration: DRKS00014619. Registered on 16 April 2018.
CRIS-Team Scopus Importer:2020-09-18
Keywords: chronic pain; green professions; internet- and mobile-based intervention; prevention; randomised controlled trial

Clinical and cost-effectiveness of guided internet-based interventions in the indicated prevention of depression in green professions (PROD-A): Study protocol of a 36-month follow-up pragmatic randomized controlled trial - Braun, Lina; Titzler, Ingrid; Ebert, David; Buntrock, Claudia; Terhorst, Yannik; Freund, Johanna; Thielecke, Janika; Baumeister, Harald (BMC Psychiatry, 2019)
Background: People in green professions are exposed to a variety of risk factors, which could possibly enhance the development of depression. Amongst possible prevention approaches, internet- and mobile-based interventions (IMIs) have been shown to be effective and scalable. However, little is known about the effectiveness in green professions. The aim of the present study is to examine the (cost-)effectiveness of a tailored IMI program for reducing depressive symptoms and preventing the onset of clinical depression compared to enhanced treatment as usual (TAU+). Methods: A pragmatic randomized controlled trial (RCT) will be conducted to evaluate a tailored and therapeutically guided preventive IMI program in comparison to TAU+ with follow-ups at post-treatment (9 weeks), 6-, 12-, 24-, and 36-months. Entrepreneurs in green professions, collaborating spouses, family members and pensioners (N = 360) with sufficient insurance status and at least subthreshold depression (PHQ-9 ≥ 5) are eligible for inclusion. Primary outcome is depressive symptom severity (QIDS-SR16). Secondary outcomes include incidence of depression (QIDS-SR16), quality of life (AQoL-8D) and negative treatment effects (INEP). A health-economic evaluation will be conducted from a societal perspective. The IMI program is provided by psychologists of an external service company and consists of six guided IMIs (6-8 modules, duration: 6-8 weeks) targeting different symptoms (depressive mood, depressive mood with comorbid diabetes, perceived stress, insomnia, panic and agoraphobic symptoms or harmful alcohol use). Intervention choice depends on a screening of participants' symptoms and individual preferences. The intervention phase is followed by a 12-months consolidating phase with monthly contact to the e-coach. Discussion: This is the first pragmatic RCT investigating long-term effectiveness of a tailored guided IMI program for depression prevention in green professions. The present trial builds on a large-scale strategy for depression prevention in green professions. The intended implementation of the IMI program with a nationwide rollout has the potential to reduce overall depression burden and associated health care costs in case of given effectiveness. Trial registration: German Clinical Trial Registration: DRKS00014000. Registered on 09 April 2018.
CRIS-Team Scopus Importer:2019-09-17
Keywords: Depression; Green professions; Internet- and mobile-based interventions; Prevention; RCT

Clinical and Cost-Effectiveness of Personalized Tele-Based Coaching for Farmers, Foresters and Gardeners to Prevent Depression: Study Protocol of an 18-Month Follow-Up Pragmatic Randomized Controlled Trial (TEC-A) - Thielecke, Janika; Buntrock, Claudia; Titzler, Ingrid; Braun, Lina; Freund, Johanna; Berking, Matthias; Baumeister, Harald; Ebert, David (Frontiers in Psychiatry, 2020)
Background: Farmers show high levels of depressive symptoms and mental health problems in various studies. This study is part of a nationwide prevention project carried out by a German social insurance company for farmers, foresters, and gardeners (SVLFG) to implement internet- and tele-based services among others to improve mental health in this population. The aim of the present study is to evaluate the (cost-)effectiveness of personalized tele-based coaching for reducing depressive symptom severity and preventing the onset of clinical depression, compared to enhanced treatment as usual.
CRIS-Team WoS Importer:2020-05-02

Comparative effectiveness of three versions of a stepped care model for insomnia differing in the amount of therapist support in internet-delivered treatment: study protocol for a pragmatic cluster randomised controlled trial (GET Sleep) - Spiegelhalder, Kai; Baumeister, Harald; Al-Kamaly, Abdulwahab; Bader, Martina; Bauereiss, Natalie; Benz, Fee; Braun, Lina; Buntrock, Claudia; Burkhardt, Maike; Cuijpers, Pim; Domschke, Katharina; Dülsen, Patrick; et al. (BMJ Open, 2022)
INTRODUCTION: It is unclear how internet-delivered cognitive-behavioural therapy for insomnia (CBT-I) can be integrated into healthcare systems, and little is known about the optimal level of therapist guidance. The aim of this study is to investigate three different versions of a stepped care model for insomnia (IG1, IG2, IG3) versus treatment as usual (TAU). IG1, IG2 and IG3 rely on treatment by general practitioners (GPs) in the entry level and differ in the amount of guidance by e-coaches in internet-delivered CBT-I. METHODS AND ANALYSIS: In this randomised controlled trial, 4268 patients meeting International Classification of Diseases, Tenth Revision (ICD-10) criteria for insomnia will be recruited. The study will use cluster randomisation of GPs with an allocation ratio of 3:3:3:1 (IG1, IG2, IG3, TAU). In step 1 of the stepped care model, GPs will deliver psychoeducational treatment; in step 2, an internet-delivered CBT-I programme will be used; in step 3, GPs will refer patients to specialised treatment. Outcomes will be collected at baseline, and 4 weeks, 12 weeks and 6 months after baseline assessment. The primary outcome is insomnia severity at 6 months. An economic evaluation will be conducted and qualitative interviews will be used to explore barriers and facilitators of the stepped care model. ETHICS AND DISSEMINATION: The study protocol was approved by the Ethics Committee of the Medical Centre-University of Freiburg. The results of the study will be published irrespective of the outcome. TRIAL REGISTRATION NUMBER: DRKS00021503.
CRIS-Team Scopus Importer:2022-08-19
Keywords: Adult psychiatry; PSYCHIATRY; SLEEP MEDICINE

COMPARE Family (Children of Mentally III Parents at Risk Evaluation): A Study Protocol for a Preventive Intervention for Children of Mentally III Parents (Triple P, Evidence-Based Program That Enhances Parentings Skills, in Addition to Gold-Standard CBT With the Mentally III Parent) in a Multicenter RCT-Part II - Stracke, Markus; Gilbert, Kristin; Kieser, Meinhard; Klose, Christina; Krisam, Johannes; Ebert, David; Buntrock, Claudia; Christiansen, Hanna (Frontiers in Psychiatry, 2019)
Background: Mental health problems are highly frequent, as well as being associated with enormous societal and economic costs and significant disability-adjusted life years. Children of parents with a mental illness (COPMI) are at a tremendously increased risk to develop disorders themselves. According to the literature, parental mental disorders launch a wave of risk factors that in turn predict the emergence of psychological problems in the offspring, and effective treatment of the parental disorder has been associated with reduced child psychopathology (launch and grow assumption). Furthermore, studies focusing on parent-child interaction demonstrate generally poorer parenting skills in parents with mental disorders, and the enhancement of such skills has been a significant mediator in improving child outcomes (parenting assumption).
CRIS-Team WoS Importer:2019-03-06

Digital prevention of depression for farmers? A qualitative study on participants' experiences regarding determinants of acceptance and satisfaction with a tailored guided internet intervention program - Freund, Johanna; Buntrock, Claudia; Braun, Lina; Thielecke, Janika; Baumeister, Harald; Berking, Matthias; Ebert, David; Titzler, Ingrid (Internet Interventions, 2022)
Introduction: Farmers, forest workers and gardeners have a higher risk of developing depression compared to other occupational populations. As part of the German pilot project "With us in balance", the potential of six guided internet- and mobile-based interventions (IMIs) to prevent depression among their insurants is examined. The IMI program is tailored to various risk factors of depression, individual symptoms, and needs. Although IMIs have been shown to be effective in reducing depressive symptoms, there is little qualitative research about the acceptance of digital preventive IMIs. The aim of this qualitative study is to gain insights into participants' experiences with the guided IMIs by focusing on determinants for acceptance and satisfaction.
CRIS-Team WoS Importer:2022-09-02

Do guided internet-based interventions result in clinically relevant changes for patients with depression? An individual participant data meta-analysis. - Karyotaki, Eirini; Ebert, David; Donkin, Liesje; Riper, Heleen; Twisk, Jos; Burger, Simone; Rozental, Alexander; Lange, Alfred; Williams, Alishia D.; Zarski, Anna-Carlotta; Geraedts, Anna; Van Straten, Annemieke; et al. (Clinical Psychology Review, 2018)
Little is known about clinically relevant changes in guided Internet-based interventions for depression. Moreover, methodological and power limitations preclude the identification of patients' groups that may benefit more from these interventions. This study aimed to investigate response rates, remission rates, and their moderators in randomized controlled trials (RCTs) comparing the effect of guided Internet-based interventions for adult depression to control groups using an individual patient data meta-analysis approach. Literature searches in PubMed, Embase, PsycINFO and Cochrane Library resulted in 13,384 abstracts from database inception to January 1, 2016. Twenty-four RCTs (4889 participants) comparing a guided Internet-based intervention with a control group contributed data to the analysis. Missing data were multiply imputed. To examine treatment outcome on response and remission, mixed-effects models with participants nested within studies were used. Response and remission rates were calculated using the Reliable Change Index. The intervention group obtained significantly higher response rates (OR = 2.49, 95% CI 2.17-2.85) and remission rates compared to controls (OR = 2.41, 95% CI 2.07-2.79). The moderator analysis indicated that older participants (OR = 1.01) and native-born participants (1.66) were more likely to respond to treatment compared to younger participants and ethnic minorities respectively. Age (OR = 1.01) and ethnicity (1.73) also moderated the effects of treatment on remission.Moreover, adults with more severe depressive symptoms at baseline were more likely to remit after receiving internet-based treatment (OR = 1.19). Guided Internet-based interventions lead to substantial positive treatment effects on treatment response and remission at post-treatment. Thus, such interventions may complement existing services for depression and potentially reduce the gap between the need and provision of evidence-based treatments.

Do Nonsuicidal Severely Depressed Individuals with Diabetes Profit from Internet-Based Guided Self-Help? Secondary Analyses of a Pragmatic Randomized Trial - Schlicker, Sandra; Weisel, Kiona; Buntrock, Claudia; Berking, Matthias; Nobis, Stephanie; Lehr, Dirk; Baumeister, Harald; Snoek, Frank J.; Riper, Heleen; Ebert, David (Journal of Diabetes Research, 2019)

Economic Evaluation of an Internet-Based Stress Management Intervention Alongside a Randomized Controlled Trial - Kählke, Fanny; Buntrock, Claudia; Smit, Filip; Berking, Matthias; Lehr, Dirk; Heber, Elena; Funk, Burkhardt; Riper, Heleen; Ebert, David (JMIR Mental Health, 2019)
Background: Work-related stress is widespread among employees and associated with high costs for German society. Internet-based stress management interventions (iSMIs) are effective in reducing such stress. However, evidence for their cost-effectiveness is scant.
CRIS-Team WoS Importer:2019-06-18

Economic evaluations of internet- and mobile-based interventions for the treatment and prevention of depression: A systematic review - Paganini, Sarah; Teigelkötter, Wiebke; Buntrock, Claudia; Baumeister, Harald (Journal of Affective Disorders, 2017)
Background: Internet- and mobile-based interventions (IMIs) targeting depression have been shown to be clinical effective and are considered a cost-effective complement to established interventions. The aim of this review was to provide an overview of the evidence for the cost-effectiveness of IMIs for the treatment and prevention of depression. Methods: A systematic database search was conducted (Medline, PsychInfo, CENTRAL, PSYNDEX, OHE HEED). Relevant articles were selected according to defined eligibility criteria. IMIs were classified as cost-effective if they were below a willingness-to-pay threshold (WTP) of €22,845 (£20,000) - €34,267 (£30,000) according to the National Institute for Health and Clinical Excellence (NICE) standard. Study quality was assessed using the Consolidated Health Economic Evaluation Reporting Standard guidelines and the Cochrane Risk of Bias Tool. Results: Of 1,538 studies, 11 economic evaluations of IMIs for the treatment of depression, and 1 for the prevention of depression, were eligible for inclusion. In 6 studies, IMIs were classified as likely to be cost-effective with an incremental cost-utility ratio between €3,088 and €22,609. All of these IMIs were guided. Overall quality of most economic evaluations was evaluated as good. All studies showed some risk of bias. Limitations: The studies used different methodologies and showed some risk of bias. These aspects as well as the classification of cost-effectiveness according to the WTP proposed by NICE should be considered when interpreting the results. Conclusions: Results indicate that guided IMIs for the treatment of (subthreshold) depression have the potential to be a cost-effective complement to already established interventions, but more methodologically sound studies are needed.
Keywords: Systematic review; cost-effectiveness; e-health; treatment; prevention; depression

Editorial: How to Help Employees Returning to Work Following Depression - Terao, Takeshi; Hori, Hikaru; Buntrock, Claudia (Frontiers in Psychiatry, 2021)
CRIS-Team WoS Importer:2021-07-23

Effectiveness and cost-effectiveness of a guided Internet- and mobile-based intervention for the indicated prevention of major depression in patients with chronic back pain-study protocol of the PROD-BP multicenter pragmatic RCT - Sander, L.; Paganini, S.; Lin, J.; Schlicker, Sandra; Ebert, David; Buntrock, Claudia; Baumeister, H. (BMC Psychiatry, 2017)
BACKGROUND Reducing the disease burden of major depressive disorder (MDD) is of major public health relevance. The prevention of depression is regarded as one possible approach to reach this goal. People with multiple risk factors for MDD such as chronic back pain and subthreshold depressive symptoms may benefit most from preventive measures. The Internet as intervention setting allows for scaling up preventive interventions on a public mental health level. METHODS This study is a multicenter pragmatic randomized controlled trial (RCT) of parallel design aiming to investigate the (cost-) effectiveness of an Internet- and mobile-based intervention (IMI) for the prevention of depression in chronic back pain patients (PROD-BP) with subthreshold depressive symptoms. eSano BackCare-DP is a guided, chronic back pain-specific depression prevention intervention based on cognitive behavioral therapy (CBT) principles comprising six weekly plus three optional modules and two booster sessions after completion of the intervention. Trained psychologists provide guidance by sending feedback messages after each module. A total of 406 patients with chronic back pain and without a depressive disorder at baseline will be recruited following orthopedic rehabilitation care and allocated to either intervention or treatment-as-usual (TAU). Primary patient-relevant endpoint of the trial is the time to onset of MDD measured by the telephone-administered Structured Clinical Interview for DSM (SCID) at baseline and 1-year post-randomization. Key secondary outcomes are health-related quality of life, depression severity, pain intensity, pain-related disability, ability to work, intervention satisfaction and adherence as well as side effects of the intervention. Online assessments take place at baseline and 9 weeks as well as 6 and 12 months post-randomization. Cox regression survival analysis will be conducted to estimate hazard ratio at 12-month follow-up. Moreover, an economic analysis will be conducted from a societal and public health perspective. DISCUSSION This is the first study examining an IMI for depression prevention in a sample of chronic pain patients. If this implementation of a depression prevention IMI into orthopedic aftercare proves effective, the intervention could be integrated into routine care with minimal costs and extended for use with other chronic diseases. Results will have implications for researchers, health care providers and public health policy makers. TRIAL REGISTRATION The trial is registered at the WHO International Clinical Trials Registry Platform via the German Clinical Studies Trial Register (DRKS): DRKS00007960 . Registered 12 August 2015.
Keywords: Prevention; RCT; eHealth; Internet and mobile based; Major depression; Chronic back pain; CBT; Effectiveness; Economic evaluation

Effectiveness of a Guided Web-Based Self-help Intervention to Prevent Depression in Patients with Persistent Back Pain: The PROD-BP Randomized Clinical Trial - Sander, Lasse B.; Paganini, Sarah; Terhorst, Yannik; Schlicker, Sandra; Lin, Jiaxi; Spanhel, Kerstin; Buntrock, Claudia; Ebert, David D.; Baumeister, Harald (JAMA Psychiatry, 2020)
Importance: Depression is a frequent comorbid condition in patients with persistent back pain and is associated with substantial adverse consequences, including the risk of developing opioid use disorders. Shifting the focus from depression treatment to preventing depression might be a viable way to reduce the disease burden. Objective: To evaluate the effectiveness of a web-based self-help intervention to reduce the incidence of major depressive episode (MDE) in patients with persistent back pain. Design, Setting, and Participants: Prevention of Depression in Back Pain Patients (PROD-BP) was a pragmatic, observer-blinded randomized clinical trial with a parallel design conducted in Germany. Eligible adults with a diagnosis of persistent back pain and subclinical depressive symptoms, but who were depression free, were recruited either on-site or after discharge from 82 orthopedic clinics between October 1, 2015, and July 31, 2017. All analyses were conducted according to the intention-to-treat principle from October 31, 2018, to April 30, 2019. Interventions: The intervention group received an e-coach-guided, web-based self-help intervention that was based on cognitive behavioral therapy and tailored to the needs of patients with persistent back pain. The intervention included 6 obligatory modules and 3 optional modules to be completed by participants as well as feedback from e-coaches. Both the intervention and control groups had unrestricted access to treatment as usual. Main Outcomes and Measures: Primary outcome was time to onset of an MDE over a 12-month period as assessed by blinded diagnostic raters using the Structured Clinical Interview for DSM-5. Secondary outcomes included depression severity, quality of life, pain intensity, pain-related disability, pain self-efficacy, work capacity, and user satisfaction assessed with a variety of instruments. Results: A total of 295 participants (mean [SD] age, 52.8 [7.7] years; 184 women [62.4%]) were recruited and randomized to either the intervention group (n = 149) or control group (n = 146). The intervention reduced the risk of MDE onset by 52% (hazard ratio, 0.48; 95% CI, 0.28-0.81; P <.001). Twenty-one participants (14.1%) in the intervention group and 41 participants (28.1%) in the control group experienced an MDE over the 12-month period. The number needed to treat to prevent 1 new case of MDE was 2.84 (95% CI, 1.79-9.44). Conclusions and Relevance: Results of this trial showed that among patients with persistent back pain, depression can be prevented by a guided web-based self-help intervention in addition to treatment as usual. This finding suggests that using a scalable digital approach to integrate psychological treatment into routine pain management is feasible. Trial Registration: German Clinical Trials Register Identifier: DRKS00007960..
CRIS-Team Scopus Importer:2020-06-09

Effectiveness of a Web-based Cognitive Behavioral Intervention for the Prevention of Depression: Pragmatic Randomized Controlled Trial - Buntrock, Claudia; Ebert, David; Lehr, Dirk; Heleen, Riper; Smit, Filip; Berking, Matthias; Cuijpers, Pim (JAMA Psychiatry, 2017)

Effectiveness of Web- and Mobile-Based Treatment of Subthreshold Depression With Adherence-Focused Guidance: A Single-Blind Randomized Controlled Trial - Ebert, David; Buntrock, Claudia; Lehr, Dirk; Smit, Filip; Riper, Heleen; Baumeister, Harald; Cuijpers, Pim; Berking, Matthias (Behavior Therapy, 2018)
Evidence for the impact of psychological Interventions for subthreshold depression (sD) is conflicting. Moreover, human resources to deliver such treatments are limited. This study aimed to evaluate the effectiveness of a web-based intervention with adherence-focused guidance in the treatment of sD. Participants with sD (CES-D. ≥ 16, no Major Depressive Disorder according to DSM-IV criteria, N = 204) recruited via a large health insurance were randomly allocated to a web-based mobile-supported cognitive-behavioral intervention or to a waitlist control condition with unrestricted access to usual care. The primary outcome was the reduction in depressive symptom severity as measured by blind diagnostic raters using the Quick Inventory of Depressive Symptomatology (QIDS) at posttreatment. There was a statistically significant between-group difference in QIDS scores at posttreatment in favor of the intervention group, F(1, 201) = 11.31, p = .001, corresponding to a medium effect size of d = 0.37 (95% CI 0.09-0.64) and a NNT of 7 (95%-CI 3.7-41.2). Significant effects in favour of the intervention group were also found for secondary outcomes such as quality of life, anxiety, and insomnia severity. Web-based self-help interventions with adherence-focused guidance could be an acceptable and effective approach to reduce a range of negative consequences associated with subclinical depressio
Keywords: Clinician-rated; Minor depression; Subthreshold depression; Web-based intervention

Effect of a web-based guided self-help intervention for prevention of major depression in adults with subthreshold depression a randomized clinical trial - Buntrock, Claudia; Ebert, David; Lehr, Dirk; Smit, Filip; Riper, Heleen; Berking, Matthias; Cuijpers, Pim (Journal of the American Medical Association, 2016)
Importance Evidence-based treatments for major depressive disorder (MDD) are not very successful in improving functional and health outcomes. Attention has increasingly been focused on the prevention of MDD. OBJECTIVE To evaluate the effectiveness of a web-based guided self-help intervention for the prevention of MDD. DESIGN, SETTING, AND PARTICIPANTS Two-group randomized clinical trial conducted between March 1, 2013, and March 4, 2015. Participants were recruited in Germany from the general population via a large statutory health insurance company (ie, insurance funded by joint employer-employee contributions). Participants included 406 self-selected adults with subthreshold depression (Centre for Epidemiologic Studies Depression Scale score≥16, no current MDD according to Diagnostic and Statistical Manual of Mental Disorders [Fourth Edition, Text Revision] criteria). INTERVENTIONS All participants had unrestricted access to usual care (visits to the primary care clinician) and were randomized to either a web-based guided self-help intervention (cognitive-behavioral and problem-solving therapy supported by an online trainer; n = 202) or a web-based psychoeducation program (n = 204). MAIN OUTCOMES AND MEASURES The primary outcome was time to onset of MDD in the intervention group relative to the control group over a 12-month follow-up period as assessed by blinded diagnostic raters using the telephone-administered Structured Clinical Interview for DSM-IV Axis Disorders at 6-and 12-month follow-up, covering the period to the previous assessment. RESULTS Among 406 randomized patients (mean age, 45 years; 73.9%women), 335 (82%) completed the telephone follow-up at 12 months. Fifty-five participants (27%) in the intervention group experienced MDD compared with 84 participants (41%) in the control group. Cox regression analyses controlling for baseline depressive symptom severity revealed a hazard ratio of 0.59 (95%CI, 0.42-0.82; P =.002) at 12-month follow-up. The number needed to treat to avoid 1 new case of MDD was 5.9 (95%CI, 3.9-14.6). CONCLUSIONS AND RELEVANCE Among patients with subthreshold depression, the use of a web-based guided self-help intervention compared with enhanced usual care reduced the incidence of MDD over 12 months. Further research is needed to understand whether the effects are generalizable to both first onset of depression and depression recurrence as well as efficacy without the use of an online trainer.

Effect of a Web-Based Guided Self-Help Intervention for Prevention of Major Depression in Adults with Subthreshold Depression: A Randomized Clinical Trial - Buntrock, Claudia; Ebert, David; Lehr, Dirk; Smit, Filip; Riper, Heleen; Berking, Matthias; Cuijpers, Pim (Obstetrical and Gynecological Survey, 2016)

Efficacy and Moderators of Internet-Based Interventions in Adults with Subthreshold Depression: An Individual Participant Data Meta-Analysis of Randomized Controlled Trials - Reins, Jo Annika; Buntrock, Claudia; Zimmermann, Johannes; Grund, Simon; Harrer, Mathias; Lehr, Dirk; Baumeister, Harald; Weisel, Kiona; Domhardt, Matthias; Imamura, Kotaro; Kawakami, Norito; Spek, Viola; et al. (Psychotherapy and Psychosomatics, 2020)
Introduction: Evidence on effects of Internet-based interventions to treat subthreshold depression (sD) and prevent the onset of major depression (MDD) is inconsistent. Objective: We conducted an individual participant data meta-analysis to determine differences between intervention and control groups (IG, CG) in depressive symptom severity (DSS), treatment response, close to symptom-free status, symptom deterioration and MDD onset as well as moderators of intervention outcomes. Methods: Randomized controlled trials were identified through systematic searches via PubMed, PsycINFO, Embase and Cochrane Library. Multilevel regression analyses were used to examine efficacy and moderators. Results: Seven trials (2,186 participants) were included. The IG was superior in DSS at all measurement points (posttreatment: 6-12 weeks; Hedges' g = 0.39 [95% CI: 0.25-0.53]; follow-up 1: 3-6 months; g = 0.30 [95% CI: 0.15-0.45]; follow-up 2: 12 months, g = 0.27 [95% CI: 0.07-0.47], compared with the CG. Significantly more participants in the IG than in the CG reached response and close to symptom-free status at all measurement points. A significant difference in symptom deterioration between the groups was found at the posttreatment assessment and follow-up 2. Incidence rates for MDD onset within 12 months were lower in the IG (19%) than in the CG (26%). Higher initial DSS and older age were identified as moderators of intervention effect on DSS. Conclusions: Our findings provide evidence for Internet-based interventions to be a suitable low-threshold intervention to treat individuals with sD and to reduce the incidence of MDD. This might be particularly true for older people with a substantial symptom burden.
CRIS-Team Scopus Importer:2020-07-10
Keywords: eHealth; Individual participant data meta-analysis; Minor depression; Moderators; Online therapy; Subclinical depression

Guided internet-based cognitive behavioral therapy for insomnia: Health-economic evaluation from the societal and public health care perspective alongside a randomized controlled trial - Buntrock, Claudia; Lehr, Dirk; Smit, Filip; Horvath, Hanne; Berking, Matthias; Spiegelhalder, Kai; Riper, Heleen; Ebert, David Daniel (Journal of Medical Internet Research, 2021)
Background: The evidence base for internet-based cognitive behavioral therapy for insomnia (iCBT-I) is firm; however, little is known about iCBT-I's health-economic effects. Objective: This study aimed to evaluate the cost-effectiveness and cost-utility of iCBT-I in reducing insomnia among schoolteachers. Methods: Schoolteachers (N=128) with clinically significant insomnia symptoms and work-related rumination were randomized to guided iCBT-I or a wait list control group, both with unrestricted access to treatment as usual. Health care use, patient and family expenditures, and productivity losses were self-assessed and used for costing from a societal and a public health care perspective. Costs were related to symptom-free status (score <8 on the insomnia severity index) and quality-adjusted life years (QALYs) gained. Sampling error was handled using nonparametric bootstrapping. Results: Statistically significant differences favoring the intervention group were found for both health outcomes (symptom-free status yes or no: β=.30; 95% CI 0.16-0.43; QALYs: β=.019, 95% CI 0.01-0.03). From a societal perspective, iCBT-I had a 94% probability of dominating the wait list control for both health outcomes. From a public health care perspective, iCBT-I was more effective but also more expensive than the wait list control, resulting in an incremental cost-effectiveness ratio of €650 per symptom-free individual. In terms of QALYs, the incremental cost-effectiveness ratio was €11, 285. At a willingness-to-pay threshold of €20, 000 per QALY gained, the intervention's probability of being cost-effective was 89%. Conclusions: Our trial indicates that iCBT could be considered as a good value-for-money intervention for insomnia.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Behavior; Cognitive behavioral therapy; Cost-effectiveness; Cost-utility; Economic evaluation; Economics; ICBT-I; Insomnia; Internet-based cognitive behavioural therapy; Perspective; Public health; Sleep

How can we estimate QALYs based on PHQ-9 scores? Equipercentile linking analysis of PHQ-9 and EQ-5D - Furukawa, Toshi A.; Levine, Stephen Z.; Buntrock, Claudia; Ebert, David D.; Gilbody, Simon; Brabyn, Sally; Kessler, David; Björkelund, Cecilia; Eriksson, Maria; Kleiboer, Annet; Van Straten, Annemieke; Riper, Heleen; et al. (Evidence-Based Mental Health, 2021)
Background Quality-Adjusted life years (QALYs) are widely used to measure the impact of various diseases on both the quality and quantity of life and in their economic valuations. It will be clinically important and informative if we can estimate QALYs based on measurements of depression severity. Objective To construct a conversion table from the Patient Health Questionnaire-9 (PHQ-9), the most frequently used depression scale in recent years, to the Euro-Qol Five Dimensions Three Levels (EQ-5D-3L), one of the most commonly used instruments to assess QALYs. Methods We obtained individual participant data of randomised controlled trials of internet cognitive-behavioural therapy which had administered depression severity scales and the EQ-5D-3L at baseline and at end of treatment. Scores from depression scales were all converted into the PHQ-9 according to the validated algorithms. We used equipercentile linking to establish correspondences between the PHQ-9 and the EQ-5D-3L. Findings Individual-level data from five trials (total N=2457) were available. Subthreshold depression (PHQ-9 scores between 5 and 10) corresponded with EQ-5D-3L index values of 0.9-0.8, mild major depression (10-15) with 0.8-0.7, moderate depression (15-20) with 0.7-0.5 and severe depression (20 or higher) with 0.6-0.0. A five-point improvement in PHQ-9 corresponded approximately with an increase in EQ-5D-3L score by 0.03 and a ten-point improvement by approximately 0.25. Conclusions and Clinical Implications The conversion table between the PHQ-9 and the EQ-5D-3L scores will enable fine-grained assessment of burden of depression at its various levels of severity and of impacts of its various treatments.
CRIS-Team Scopus Importer:2021-08-06
Keywords: depression & mood disorders

How to promote usage of telehealth interventions for farmers' mental health? A qualitative study on supporting and hindering aspects for acceptance and satisfaction with a personalized telephone coaching for depression prevention - Thielecke, Janika; Buntrock, Claudia; Freund, Johanna; Braun, Lina; Ebert, David D.; Berking, Matthias; Baumeister, Harald; Titzler, Ingrid (Internet Interventions, 2023)
Low-threshold and remotely delivered preventive interventions, like telephone coaching, are warranted for farmers who experience multiple risk factors for depression, live in underserved areas, and show low help-seeking behavior. Factors facilitating uptake and actual use of effective remote interventions are important to reduce depression disease burden. This study aimed at identifying factors that potentially can influence acceptance of and satisfaction with a telephone coaching in this occupational group. Semi-structured interviews were based on the ‘Unified Theory of Acceptance and Use of Technology’, the ‘Evaluation’, and ‘Discrepancy’ models for satisfaction. Interviews were conducted with 20 of 66 invited participants of a 6-months telephone coaching during an effectiveness or implementation study. Audio-recorded interviews were transcribed and analyzed (deductive-inductive qualitative content analysis). Independent coding by two persons resulted in good agreement (Κ = 0.80). Participants validated results via questionnaire. Overall, 32 supporting (SF) and 14 hindering factors (HF) for acceptance and satisfaction were identified and organized into five dimensions: Coaching result (SF = 9, HF = 3), coach (SF = 9, HF = 1), organization (SF = 5, HF = 2), the telephone as communication medium (SF = 4, HF = 5) and participant characteristics (SF = 5, HF = 3). Most named SFs were ‘Flexible appointment arrangement’ (n = 19/95 %) and ‘low effort’ (n = 17/85 %), while most reported HFs were ‘lack of visual cues’ (n = 12/60 %) and ‘social/professional involvement restricts change process’ (n = 10/50 %). The perceived changes initiated by coaching, a low effort through telephone conduct, and the indicated personalization were identified as important influencing factors on acceptance and satisfaction based on interviewees' statements. Both may be further enhanced by offering choice and advice for delivery formats (e.g., video-calls) and training of coaches in farm-related issues. Study registration: German Clinical Trial Registrations: DRKS00017078 and DRKS00015655.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Acceptance; Depression; Farmers; Interviews; Satisfaction; Telephone coaching

How to reach the Farmers for Participation in digital Prevention Services: 'Lessons learned' from a national Depression Prevention Project - Thielecke, Janika; Freund, Johanna; Buntrock, Claudia; Braun, L.; Baumeister, H.; Berking, Matthias; Ebert, D. D.; Titzler, Ingrid (GESUNDHEITSWESEN, 2022)
CRIS-Team WoS Importer:2022-09-16

Increasing the clinical interpretability of PHQ-9 through equipercentile linking with health utility values by EQ-5D-3L - Furukawa, Toshi A.; Levine, Stephen Z.; Buntrock, Claudia; Cuijpers, Pim (Evidence-Based Mental Health, 2021)
CRIS-Team Scopus Importer:2021-08-06
Keywords: adult psychiatry; anxiety disorders; psychiatry

Individual Case Coaching through Telephone as a Prevention Offer for Farmers, Foresters and Horticulturists? - Results of a randomized controlled Efficacy Trial (TEC-A) - Thielecke, Janika; Buntrock, Claudia; Titzler, Ingrid; Freund, Johanna; Braun, L.; Baumeister, H.; Ebert, David (GESUNDHEITSWESEN, 2021)
CRIS-Team WoS Importer:2022-05-20

Internet-Based Cognitive Behavioral Therapy for Insomnia: A Health Economic Evaluation - Thiart, Hanne; Ebert, David; Lehr, Dirk; Nobis, Stephanie; Buntrock, Claudia; Berking, Matthias; Smit, Filip; Riper, Heleen (Sleep, 2016)
Conclusions: Focusing on sleep improvement using iCBT-I may be a cost-effective strategy in occupational health care.
Keywords: cost-benefit; cost-effectiveness; employer perspective; insomnia; Internet; randomized controlled trial; self-help; cost-benefit; cost-effectiveness; employer perspective; insomnia; Internet; randomized controlled trial; self-help

Lessons learned from an attempted randomized-controlled feasibility trial on “WIDeCAD” - An internet-based depression treatment for people living with coronary artery disease (CAD) - Bendig, Eileen; Bauereiß, Natalie; Buntrock, Claudia; Habibović, Mirela; Ebert, David Daniel; Baumeister, Harald (Internet Interventions, 2021)
Background: Despite the high prevalence of comorbid depression in people living with coronary artery disease (CAD), uptake of psychological treatment is generally low. This study was designed to investigate the feasibility of an internet-based cognitive-behavioral (iCBT) depression intervention for people with CAD and depressive symptoms. Methods: People with CAD and depressive symptoms (PHQ-9 ≥ 5) were randomly assigned to the eight modules comprising iCBT (N = 18), or waitlist-control (N = 16). Measures were taken at baseline (t1) and at post-treatment (eight weeks after randomization, t2). Feasibility-related outcomes were recruitment strategy, study attrition, intervention dropout, satisfaction, negative effects as well as the potential of the intervention to affect likely outcomes in a future full-scale trial (depression, anxiety, quality of life, fear of progression). Data analyses were based on intention-to-treat principles. Linear regression models were used to detect between group differences. Linear Mixed Models were used to model potential changes over time. Results: This trial was terminated prior to a-priori defined sample size has been reached given low recruitment success as well as high intervention dropout (88%) and study attrition (23%). On average, participants in the intervention group completed M = 2.78 (SD = 3.23) modules. Participants in the waitlist control group barely started one module (M = 0.82, SD = 1.81). The satisfaction with the intervention was low (M = 20.6, SD = 0.88). Participants reported no negative effects attributed to the iCBT. Differences between groups with regard to depression, anxiety, fear of progression and quality of life remained non-significant (p > 0.05). Conclusion: This trial failed to recruit a sufficient number of participants. Future work should explore potential pitfalls with regards to the reach and persuasiveness of internet interventions for people living with CAD. The study gives important indications for future studies with regard to the need for new ideas to reach and treat people with CAD and depression.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Cognitive behavioral therapy; Coronary artery disease; Depression; Internet and mobile-based intervention; Psychological intervention

Mediators and mechanisms of change in internet- and mobile-based interventions for depression: A systematic review - Domhardt, Matthias; Steubl, Lena; Boettcher, Johanna; Buntrock, Claudia; Karyotaki, Eirini; Ebert, David D.; Cuijpers, Pim; Baumeister, Harald (Clinical Psychology Review, 2021)
The efficacy of Internet- and mobile-based interventions (IMIs) for depression in adults is well established. Yet, comprehensive knowledge on the mediators responsible for therapeutic change in these interventions is pending. Therefore, we conducted the first systematic review on mediators in IMIs for depression, investigating mechanisms of change in interventions with different theoretical backgrounds and delivery modes (PROSPERO CRD42019130301). Two independent reviewers screened references from five databases (i.e., Cochrane Library, Embase, MEDLINE/PubMed, PsycINFO and ICTRP), selected studies for inclusion and extracted data from eligible studies. We included 26 RCTs on mediators in IMIs for depression (6820 participants), rated their risk of bias and adherence to methodological quality criteria for psychotherapy process research. Primary studies examined 64 mediators, with cognitive variables (e.g., perceived control, rumination or interpretation bias) being the largest group of both examined (m = 28) and significant mediators (m = 22); followed by a range of other mediators, including mindfulness, acceptance and behavioral activation. Our findings might contribute to the empirically-informed advancement of interventions and mental health care practices, enabling optimized treatment outcomes for patients with depression. Furthermore, we discuss implications for future research and provide methodological recommendations for forthcoming mediation studies with more pertinent designs, allowing for inferences with higher causal specificity.
CRIS-Team Scopus Importer:2021-01-22
Keywords: Depression; Digital intervention; e- and m-Health; Mechanism of change; Process research; Psychotherapy

Moderators of psychological and psychoeducational interventions for the prevention of depression: A systematic review - Conejo-Cerón, Sonia; Bellón, Juan Ángel; Motrico, Emma; Campos-Paíno, Henar; Martín-Gómez, Carmen; Ebert, David; Buntrock, Claudia; Gili, Margalida; Moreno-Peral, Patricia (Clinical Psychology Review, 2020)
Psychological and psychoeducational interventions have proven to be effective in preventing depression. However, the identification of the patients that benefit the most from each type of intervention has not yet been established. A systematic review was performed of the literature on moderators of preventive psychological and psychoeducational interventions for depression in all types of population. A search was performed on PubMed, PsycINFO, Web of Science, Embase, Cochrane Central Register of Controlled Trials and OpenGrey up to July 2019. Fulfillment of eligibility criteria, data collection, and study quality assessment were assessed by two independent researchers. Outcomes were moderators of the reduction of depressive symptoms or the incidence of depression. Twenty-seven moderator effect studies performed in 19 randomized controlled trials were included. Thirty-four potential sociodemographic, clinical, interpersonal, personality and life-event moderators were evaluated. Baseline depressive symptoms, gender, age, baseline parental depression and social support were the most frequently studied potential moderators. In interventions for children and adolescents, the moderator for which evidence was strongest was having parents free of depression at baseline. Psychological and psychoeducational interventions seem to be more effective in children and adolescents who exhibit a lower use of substances and whose parents do not have symptoms of depression at baseline. In adults, a lower age was associated with greater effects of preventive interventions. Ethics: As this systematic review is based on published data, approval from the local ethics committee was not required.
CRIS-Team Scopus Importer:2020-06-09
Keywords: Depression; Moderator; Prevention; Systematic review

@myTabu—A Placebo Controlled Randomized Trial of a Guided Web-Based Intervention for Individuals Who Sexually Abused Children and Individuals Who Consumed Child Sexual Exploitation Material: A Clinical Study Protocol - Fromberger, Peter; Schroeder, Sonja; Bauer, Louisa; Siegel, Bruno; Tozdan, Safiye; Briken, Peer; Buntrock, Claudia; Etzler, Sonja; Rettenberger, Martin; Leha, Andreas; Mueller, Juergen L. (Frontiers in Psychiatry, 2021)
Background: There is a high demand for evidence-based and cost-effective treatment concepts for convicted individuals who sexually abused children (ISAC) and individuals who consumed child sexual exploitation material (ICCSEM) under community supervision (CS). The @myTabu-consortium developed a guided web-based intervention for convicted ISAC and ICCSEM under CS consisting of six online modules targeting psychological meaningful risk factors. The study aims to evaluate the effectiveness of this guided web-based intervention in reducing dynamic risk factors and the risk to re-offend compared to a placebo condition. Furthermore, these dynamic risk factors are measured before and after every module to evaluate their individual effectiveness to reduce the respective risk factor as well as risk to re-offend. This clinical trial protocol describes the planned methods as well as the intervention concept. Methods: The methodological design is a placebo controlled randomized add-on trial (N = 582) with follow-ups at 8 points in time. The placebo condition controls for attention and expectation effects and comprises the same amount of modules with a comparable temporal effort as the experimental intervention. The trial is conducted as an add-on to community supervision as usually done. Primary outcomes are dynamic risk factors assessed by self-report risk assessment tools and officially recorded re-offenses. Discussion: To the best of our knowledge, the study is the first to compare the (cost-) effectiveness of a guided web-based intervention for convicted ISAC and ICCSEM under community supervision against a placebo condition. Methodological limitations (e.g., potential ceiling- or volunteers-effects) are discussed. Clinical Trial Registration: German Clinical Trial Register (DRKS 00021256). Prospectively registered: 24.04.2020.
CRIS-Team Scopus Importer:2021-02-05
Keywords: child exploitation material offenders; child sexual abuse (CSA); eHealth; randomized placebo controlled trial; web-based intervention

Online intervention for prevention of major depression: In Reply - Ebert, David; Buntrock, Claudia; Cuijpers, Pim; Berking, Matthias (Journal of the American Medical Association, 2016)

Prediction of major depressive disorder onset in college students - Ebert, David; Buntrock, Claudia; Mortier, Philippe; Auerbach, Randy; Weisel, Kiona K.; Kessler, Ronald C.; Cuijpers, Pim; Green, Jennifer G.; Kiekens, Glenn; Nock, Matthew K.; Demyttenaere, Koen; Bruffaerts, Ronny (Depression and Anxiety, 2019)
Background: Major depressive disorder (MDD) in college students is associated with substantial burden. Aims: To assess 1-year incidence of MDD among incoming freshmen and predictors of MDD-incidence in a representative sample of students. Method: Prospective cohort study of first-year college students (baseline: n = 2,519, 1-year follow-up: n = 958). Results: The incidence of MDD within the first year of college was 6.9% (SE = 0.8). The most important individual-level predictors of onset were prior suicide plans and/or attempts (OR = 9.5). The strongest population-level baseline predictors were history of childhood–adolescent trauma, stressful experience in the past 12 months, parental psychopathology, and other 12-month mental disorder. Multivariate cross-validated prediction (cross-validated AUC = 0.73) suggest that 36.1% of incident MDD cases in a replication sample would occur among the 10% of students at highest predicted risk (24.5% predicted incidence in this highest-risk subgroup). Conclusions: Screening at college entrance is a promising strategy to identify students at risk of MDD onset, which may improve the development and deployment of targeted preventive interventions.
CRIS-Team Scopus Importer:2019-05-02
Keywords: depression; epidemiology; health services; mood disorders; suicide/self-harm

Preventing Depression in Adults With Subthreshold Depression: Health-Economic Evaluation Alongside a Pragmatic Randomized Controlled Trial of a Web-Based Intervention - Buntrock, Claudia; Berking, Matthias; Smit, Filip; Lehr, Dirk; Nobis, Stephanie; Riper, Heleen; Cuijpers, Pim; Ebert, David (Journal of Medical Internet Research, 2017)
Background: Psychological interventions for the prevention of depression might be a cost-effective way to reduce the burden associated with depressive disorders. Objective: To evaluate the cost-effectiveness of a Web-based guided self-help intervention to prevent major depressive disorder (MDD) in people with subthreshold depression (sD). Methods: A pragmatic randomized controlled trial was conducted with follow-up at 12 months. Participants were recruited from the general population via a large statutory health insurance company and an open access website. Participants were randomized to a Web-based guided self-help intervention (ie, cognitive-behavioral therapy and problem-solving therapy assisted by supervised graduate students or health care professionals) in addition to usual care or to usual care supplemented with Web-based psycho-education (enhanced usual care). Depression-free years (DFYs) were assessed by blinded diagnostic raters using the telephone-administered Structured Clinical Interview for DSM-IV Axis Disorders at 6- and 12-month follow-up, covering the period to the previous assessment. Costs were self-assessed through a questionnaire. Costs measured from a societal and health care perspective were related to DFYs and quality-adjusted life years (QALYs). Results: In total, 406 participants were enrolled in the trial. The mean treatment duration was 5.84 (SD 4.37) weeks. On average, participants completed 4.93 of 6 sessions. Significantly more DFYs were gained in the intervention group (0.82 vs 0.70). Likewise, QALY health gains were in favor of the intervention, but only statistically significant when measured with the more sensitive SF-6D. The incremental per-participant costs were €136 (£116). Taking the health care perspective and assuming a willingness-to-pay of €20,000 (£17,000), the intervention’s likelihood of being cost-effective was 99% for gaining a DFY and 64% or 99% for gaining an EQ-5D or a SF-6D QALY. Conclusions: Our study supports guidelines recommending Web-based treatment for sD and adds that this not only restores health in people with sD, but additionally reduces the risk of developing a MDD. Offering the intervention has an acceptable likelihood of being more cost-effective than enhanced usual care and could therefore reach community members on a wider scale. Trial registration: German Clinical Trials Register: DRKS00004709; http://www.drks.de/DRKS00004709 (Archived by WebCite at http://www.webcitation.org/6kAZVUxy9)
Keywords: prevention; major depressive disorders; Internet; early intervention; cost effectiveness

Preventing the onset of major depressive disorder: a meta-analytic review of psychological interventions. - Van Zoonen, Kim; Buntrock, Claudia; Ebert, David; Smit, Filip; Reynolds, Charles F.; Beekman, Aartjan T. F.; Cuijpers, Pim (International Journal of Epidemiology, 2014)
BACKGROUND Depressive disorders are highly prevalent, have a detrimental impact on the quality of life of patients and their relatives and are associated with increased mortality rates, high levels of service use and substantial economic costs. Current treatments are estimated to only reduce about one-third of the disease burden of depressive disorders. Prevention may be an alternative strategy to further reduce the disease burden of depression. METHODS We conducted a meta-analysis of randomized controlled trials examining the effects of preventive interventions in participants with no diagnosed depression at baseline on the incidence of diagnosed depressive disorders at follow-up. We identified 32 studies that met our inclusion criteria. RESULTS We found that the relative risk of developing a depressive disorder was incidence rate ratio = 0.79 (95% confidence interval: 0.69-0.91), indicating a 21% decrease in incidence in prevention groups in comparison with control groups. Heterogeneity was low (I(2) = 24%). The number needed to treat (NNT) to prevent one new case of depressive disorder was 20. Sensitivity analyses revealed no differences between type of prevention (e.g. selective, indicated or universal) nor between type of intervention (e.g. cognitive behavioural therapy, interpersonal psychotherapy or other). However, data on NNT did show differences. CONCLUSIONS Prevention of depression seems feasible and may, in addition to treatment, be an effective way to delay or prevent the onset of depressive disorders. Preventing or delaying these disorders may contribute to the further reduction of the disease burden and the economic costs associated with depressive disorders.

Reducing problematic alcohol use in employees: economic evaluation of guided and unguided web-based interventions alongside a three-arm randomized controlled trial - Buntrock, Claudia; Freund, Johanna; Smit, Filip; Riper, Heleen; Lehr, Dirk; Boss, Leif; Berking, Matthias; Ebert, David Daniel (Addiction, 2021)
Aims: To perform an economic evaluation of guided and unguided internet-based interventions to reduce problematic alcohol consumption in employees compared with a waiting-list control condition (WLC) with unrestricted access to treatment-as-usual. Design: A cost-effectiveness analysis (CEA) and cost–utility analysis (CUA) from a societal and a cost–benefit analysis from the employer's perspective with a 6-month time horizon. Setting: Open recruitment in the German working population. Participants: Employees (178 males, 256 females, mean age 47 years) consuming at least 14 (women) or 21 (men) standard units of alcohol (SUAs) per week and scoring ≥ 8 (men) or 6 (women) on the Alcohol Use Disorders Identification Test. Measurements: On-line questionnaires administered to assess SUAs and assess quality of life (AQoL-8D) and resource use. Outcome measure was responder (≤ 14/≤ 21 SUAs) for the CEA and quality-adjusted life years (QALYs) for the CUA. Net benefit regression was used to estimate cost-effectiveness for each study arm. Bootstrapping and sensitivity analyses were performed to account for uncertainty. Interventions: Five weekly modules including personalized normative feedback, motivational interviewing, goal setting, problem-solving and emotion regulation, provided with adherence-focused guidance [n = 142; responders: n = 73 (51.4%); QALYs = 0.364, standard error (SE) = 0.006] or without guidance [n = 146; n = 66 (45.2%); 0.359, 0.007]. Controls were on a waiting-list [n = 144; n = 38 (26.4%); 0.342, 0.007]. Findings: From a societal perspective, the guided intervention had a probability of 55% (54%) of being the most efficient strategy at a willingness-to-pay (WTP) of €0 per responder (QALY) gained, compared with the unguided intervention and the control condition. At a WTP of €20 000 per QALY gained, the probability was 78%. From an employer's perspective, the guided intervention had a higher probability of a positive return on investment (81%) compared with the unguided intervention (58%). Conclusion: A guided internet-based intervention to reduce problematic alcohol consumption in employees appears to be both cost-beneficial and cost-effective.
CRIS-Team Scopus Importer:2021-11-12
Keywords: Cost-effectiveness; cost–utility; economic evaluation; employees; internet-based intervention; problematic alcohol consumption; QALY

Telephone coaching for the prevention of depression in depression in farmers: Results from a pragmatic from a pragmatic randomized controlled trial - Thielecke, Janika; Buntrock, Claudia; Titzler, Ingrid; Braun, Lina; Freund, Johanna; Berking, Matthias; Baumeister, Harald; Ebert, David D. (Journal of Telemedicine and Telecare, 2022)
Introduction Farmers have a high risk for depression (MDD). Preventive measures targeting this often remotely living population might reduce depression burden. The study aimed to evaluate the effectiveness of personalized telephone coaching in reducing depressive symptom severity and preventing MDD in farmers compared to enhanced treatment as usual (TAU + ). Methods In a two-armed, pragmatic randomized controlled trial (N = 314) with post-treatment at 6 months, farming entrepreneurs, collaborating family members and pensioners with elevated depressive symptoms (PHQ-9 >= 5) were randomized to personalized telephone coaching or TAU + . The coaching was provided by psychologists and consists on average of 13 (+/- 7) sessions a 48 min (+/- 15) over 6 months. The primary outcome was depressive symptom severity (QIDS-SR16). Results Coaching participants showed a significantly greater reduction in depressive symptom severity compared to TAU + (d = 0.39). Whereas reliable symptom deterioration was significantly lower in the intervention group compared to TAU + , no significant group differences were found for reliable improvement and in depression onset. Further significant effects in favor of the intervention group were found for stress (d = 0.34), anxiety (d = 0.30), somatic symptoms (d = 0.39), burnout risk (d = 0.24-0.40) and quality of life (d = 0.28). Discussion Limiting, we did not apply an upper cutoff score for depressive symptom severity or controlled for previous MDD episodes, leaving open whether the coaching was recurrence/relapse prevention or early treatment. Nevertheless, personalized telephone coaching can effectively improve mental health in farmers. It could play an important role in intervening at an early stage of mental health problems and reducing disease burden related to MDD.
CRIS-Team WoS Importer:2022-07-01

Turning good intentions into actions by using the health action process approach to predict adherence to internet-based depression prevention: Secondary analysis of a randomized controlled trial - Zarski, Anna-Carlotta; Berking, Matthias; Reis, Dorota; Lehr, Dirk; Buntrock, Claudia; Schwarzer, Ralf; Ebert, David (Journal of Medical Internet Research, 2018)
Keywords: Adherence; Depression prevention; Health action process approach; Internet Intervention

Was beeinflusst die Akzeptanz und Zufriedenheit mit einem telefonischen Einzelfallcoaching zur Prävention von Depression in der Landwirtschaft? – Qualitative Interviews mit teilnehmenden Personen aus den grünen Berufen - Thielecke, Janika; Buntrock, Claudia; Freund, Johanna; Braun, Lina; Berking, Matthias; Baumeister, Harald; Ebert, David D.; Titzler, Ingrid (Gesundheitswesen, 2022)
Bei Landwirten und anderen grünen Berufen treffen Risikofaktoren für Depressionen (u. a. saisonale Arbeit, unvorhersehbare Wetterbedingungen) auf ein geringes Hilfesuchverhalten und unzureichende Gesundheitsversorgung im ländlichen Raum. Digitale Angebote zur Prävention von Depression, welche auf die Zielgruppe ausgerichtet sind, können die mentale Gesundheit in den grünen Berufen fördern. Um jedoch ihr volles Potential in der Gesundheitsversorgung entfalten zu können, müssen Faktoren identifiziert werden, die eine langfristige und flächendeckende Implementierung unterstützen. Diese Studie zielte daher darauf ab, Aspekte zu identifizieren, welche die Akzeptanz und Zufriedenheit mit einem präventiven Telefoncoaching in den grünen Berufen beeinflussen.<br

Web-based intervention for depressive symptoms in adults with type 1 and type 2 diabetes mellitus - Nobis, Stephanie; Ebert, David; Lehr, Dirk; Smit, Filip; Buntrock, Claudia; Baumeister, Harald; Snoek, Frank; Berking, Matthias (British Journal of Psychiatry, 2017)